2022
DOI: 10.1038/s41419-022-05445-w
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem/stromal cells primed by inflammatory cytokines alleviate psoriasis-like inflammation via the TSG-6-neutrophil axis

Abstract: Psoriasis is currently an incurable skin disorder mainly driven by a chronic inflammatory response. We found that subcutaneous application of umbilical cord- derived mesenchymal stem/stromal cells (MSCs) primed by IFN-γ and TNF-α, referred to as MSCs-IT, exhibited remarkable therapeutic efficacy on imiquimod (IMQ)-induced psoriasis-like inflammation in mice. Neutrophil infiltration, a hallmark of psoriasis, was significantly reduced after treatment with MSCs-IT. We further demonstrated that the effects of MSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
(57 reference statements)
0
8
1
Order By: Relevance
“… [ 41 , 42 ] S1P Keratinocytes S1P lyase is a modulating factor for proliferation and differentiation, and support its potential as a therapeutic target for psoriasis in human keratinocytes. [ 43 ] Cathepsin B Keratinocytes Cathepsin B might be a promising therapeutic target for psoriasis-like lesion, which helps to develop an anti-psoriatic agent [ 44 ] Gasdermin D Keratinocytes Targeted focal death could be considered a therapeutic strategy for psoriasis [ 48 ] AQP1 Endothelial cells The present study confirms that AQP1 is a pro-angiogenic protein and therefore may be a candidate target for anti-angiogenic molecules [ 49 ] HIF-1α Keratinocytes May provide insights into the pathophysiology of neuro inflammatory skin diseases such as psoriasis [ 50 ] EDIL3 αvβ3- FAK/MEK/ERK Endothelial cells EDIL3 and αvβ3- FAK/MEK/ERK signaling pathways will provide valuable therapeutic targets for controlling angiogenesis [ 53 ] TSG-6 Neutrophils Blocking neutrophil recruitment by MSCs-IT or TSG-6 has potential for therapeutic application in human psoriasis. [ 54 , 69 ] USP15 Keratinocytes USP15 may be a potential target for the treatment of psoriasis [ 56–58 ] NFKBIZ ...…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“… [ 41 , 42 ] S1P Keratinocytes S1P lyase is a modulating factor for proliferation and differentiation, and support its potential as a therapeutic target for psoriasis in human keratinocytes. [ 43 ] Cathepsin B Keratinocytes Cathepsin B might be a promising therapeutic target for psoriasis-like lesion, which helps to develop an anti-psoriatic agent [ 44 ] Gasdermin D Keratinocytes Targeted focal death could be considered a therapeutic strategy for psoriasis [ 48 ] AQP1 Endothelial cells The present study confirms that AQP1 is a pro-angiogenic protein and therefore may be a candidate target for anti-angiogenic molecules [ 49 ] HIF-1α Keratinocytes May provide insights into the pathophysiology of neuro inflammatory skin diseases such as psoriasis [ 50 ] EDIL3 αvβ3- FAK/MEK/ERK Endothelial cells EDIL3 and αvβ3- FAK/MEK/ERK signaling pathways will provide valuable therapeutic targets for controlling angiogenesis [ 53 ] TSG-6 Neutrophils Blocking neutrophil recruitment by MSCs-IT or TSG-6 has potential for therapeutic application in human psoriasis. [ 54 , 69 ] USP15 Keratinocytes USP15 may be a potential target for the treatment of psoriasis [ 56–58 ] NFKBIZ ...…”
Section: Discussionmentioning
confidence: 59%
“…This finding confirms the potential therapeutic application of blocking neutrophil recruitment via MSCs-IT or TSG-6 in the treatment of psoriasis. 53 Knockout of Ubiquitin Specific Peptidase 15 ( USP15 ) results in reduced inflammation in psoriatic keratinocytes, as well as impaired vitality and clonogenicity. Topical application of USP15 small interfering RNA significantly improves imiquimod (IMQ)-induced psoriatic dermatitis by reducing the infiltration of T cells and neutrophils.…”
Section: Regulating Inflammatory Cells Reducing Inflammatory Cell Inf...mentioning
confidence: 99%
“…Previous study found that TSG-6 exerts a powerful therapeutic effect in a variety of diseases such as arthritis, 32 keratitis, 33 and ulcerative colitis. 34 Exogenous TSG-6 could inhibit neutrophil infiltration and reduce the production of cytokines and chemokines, 35 thereby limiting the tissue damage caused by excessive inflammatory response. In our study, TSG-6 significantly reduced CD3+ T lymphocyte and F4/80+ inflammatory cell infiltration in the orbital and thyroid tissues of TAO model mice by intravenous administration and the effect was comparable to that of dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…TSG-6, a 30-kDa secreted glycoprotein, in uences intercellular 3D structures and remodels the extracellular matrix (ECM) through binding with hyaluronic acid, chondroitin sulfate and proteoglycan [16]. More importantly, it possesses the prominent anti-in ammatory capacity and instructs the immunoregulatory properties of MSCs in an array of diseases, including myocardial infarction, acute lung injury (ALI) and psoriasis [17][18][19]. In one instance, TSG-6 competitively conjugates the cell-surface glycosaminoglycan (GAG) binding site of CXCL8 against heparin, thereby inhibiting the in ltration of neutrophils into sites of in ammation [20].…”
Section: Introductionmentioning
confidence: 99%